Referenciação em gênero discursivo : uma proposta de trabalho com anáfora direta em produção de texto dissertativo - Santana, Gilvan da Costa (2015)
The written Portuguese Language teaching should imply the analysis of expressive features present in each individual context. This is the need to approach writing as a process, the result of a process of reflection on language and knowledge of the constitution and functioning of the language. What should carry is a productive education for the acquisition and improvement of language skills. To achieve the objectives of this project, have been developed as primarily theoretical studies involving the following: speech genres and multimodality; portuguese language teaching from the perspective of the PCN; processes, resources and referral mechanisms. That said, in this TCF, it is made a reflection on language and its realization, starting with texts, referring expressions and situations of construction of textuality. All this culminates in the didactic proposal to provide the contact opportunity of students with referral as a discursive process of building texts, making use of activities that lead students to operate this feature. The use of referral is one of the common problems in the establishment of cohesion and coherence in texts produced by students of ninth grade. With our experience, we aim to contribute to understanding and application of such a process towards collaboration in search of resolving difficulties of teacher and student in didactic teaching approach in terms of this aspect of textual production. Along the way, we come to some very relevant clarifications. Highlighting them: on anaphora as referral process, we need to deconstruct the idea that conceives the pronoun as the only part of speech that can be constituted as anaphoric; anaphora is a textual semantic phenomenon not only coreferential (direct anaphora - cotextual) but also inferential (indirect anaphora - contextual); key is to be built significant referral chains, establishing cohesive unit through this procedure.